Voice and argument structure in Baltic - Holvoet, Axel; Nau, Nicole (Valency, argument realization and grammatical relations in Baltic ;, 2015)
The present article discusses the nature of the Latvian passive and, more specifically, the impersonal passive. It is argued that Latvian has indeed an impersonal passive that shows no signs of turning into an active impersonal, a development that has occurred in the history of Polish and could be an ongoing process in contemporary Lithuanian. Several lexical restrictions on the derivation of the Latvian constructions under discussion shows that they are indeed impersonal passives rather than active impersonals. Conspicuously absent, however, is a ban on the passivization of unaccusatives, as.